1981
DOI: 10.1002/cber.19811140515
|View full text |Cite
|
Sign up to set email alerts
|

Thermische Umlagerungen von 1‐Allyloxy‐ und 1‐Propargyloxy λ5‐phosphorin‐Derivaten

Abstract: Rontgenstrukturanalyse sowie die eindeutigen Deuterierungsergebnisse sprechen fur einen stereochemisch einheitlichen Verlauf der Umlagerungen. Sterische und elektronische Einflusse auf einige analoge Umlagerungen werden untersucht, der Mechanisnus wird diskutiert.Thermal Rearrangements of 1-Allyloxy-and I-Propargyloxy-A5-phosphorin Derivatives The thermal rearrangements of l-allyloxy-h'-phosphorin derivatives 1 affords -contrary to the formally similar Claisen rearrangement of ally1 phenyl ethers -in the irrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…3,5-Sigmatropic shifts have occasionally been proposed as steps in complex rearrangement reactions' but in only one case has the process been studied in isolation and evidence for a concerted reaction been obtained. 2 The process may operate in another fairly simple case3 but in other molecules where such rearrangement might have occurred it was not observed. 4 We describe rearrangement of the 7-vinylnorcaradienes (1) to give the 8,9-dihydroindenes (2) and bicyclo[3.2.2]nonatrienes (3) and evidence that formation of the dihydroindenes involves 3,5-sigmatropy (1; arrows) rather than simple vinylcyclopropane rearrangement.…”
mentioning
confidence: 96%
“…3,5-Sigmatropic shifts have occasionally been proposed as steps in complex rearrangement reactions' but in only one case has the process been studied in isolation and evidence for a concerted reaction been obtained. 2 The process may operate in another fairly simple case3 but in other molecules where such rearrangement might have occurred it was not observed. 4 We describe rearrangement of the 7-vinylnorcaradienes (1) to give the 8,9-dihydroindenes (2) and bicyclo[3.2.2]nonatrienes (3) and evidence that formation of the dihydroindenes involves 3,5-sigmatropy (1; arrows) rather than simple vinylcyclopropane rearrangement.…”
mentioning
confidence: 96%
“…The earliest characterized example of a phosphonium ylide rearrangement was reported by Baldwin and Armstrong who demonstrated that upon heating, ylide 1 underwent a [2,3]-rearrangement to provide a 7% yield of 2 , along with a number of additional products (Figure ) . Little progress has since been reported, likely due to the apparent propensity of phosphonium ylides to undergo decomposition at the temperatures required for rearrangement. 1c, We hypothesized that structures such as 3 containing an allyloxy substituent would undergo a [3,3]-rearrangement in which the product 4 would be favored thermodynamically due to the formation of the PO bond. In addition, incorporation of the oxygen should increase the leaving group ability of the phosphorus-containing moiety, thus lowering the energetic barrier of the rearrangement …”
mentioning
confidence: 99%